The Media and Shaping the Public's Mental Image towards the Transitional Justice - Laith Abbas, Zainab (ALBAHITH ALALAMI, 2014)
Media plays an important role in shaping the mental image of their audiences for individuals, groups and organizations, States and peoples. It is the window through which overlooks the masses on events and issues, and in the light of their exposure to these means are their opinions and impressions.Despite the importance of direct experiences in shaping opinions, drawing pictures and impressions, it is inevitable to rely on these means as individuals can not engage in direct experiences with thousands of events, issues and topics that concern their community and other societies.There is no doubt that media is of great importance at the present time, because of its significant impact in the management of the course of political life, social and economic, especially during crises, wars and exceptional circumstances that may pass by any country, which will be reflected in turn on the values ​​and attitudes of society.So, shall take into account the role that posed by these media, media play an active role in various fields, including:Therefore, we must take into account the role of these media. Media is an active role in various fields, including:• Exposing the wrong practices of the rulers, and highlighting the areas of error and mistake in their actions.• Educating and guiding people by giving them ready-made ideas and declared and associated methods of persuasion.Therefore, modern media has become a necessity of contemporary life. And its use in defending opinion and belief and the cause of existence is inevitable. If such a tool lags behind, many rights are distorted or lose their right. The media is a tool of politics that can influence people's minds and attitudes.